2019
DOI: 10.3390/ijms20030634
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical and Pharmacological Properties of Ozone: The Smell of Protection in Acute and Chronic Diseases

Abstract: Ozone therapy has been widely used in everyday clinical practice over the last few years, leading to significant clinical results in the treatment of herniated discs and pain management. Nevertheless, further studies have demonstrated its potential efficacy and safety under other clinical and experimental conditions. However, some of these studies showed controversial results regarding the safety and efficacy of ozone therapy, thus mining its potential use in an everyday clinical practice. To this regard, it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 60 publications
1
63
0
13
Order By: Relevance
“…High doses of ozone induce the gene transcription of the pro-inflammatory cytokine, its receptor, and inflammatory proteins. At the same time, they invoke a negative regulation of type 1 Interferon and the response to viral infections pathways [79].…”
Section: In Vitromentioning
confidence: 99%
“…High doses of ozone induce the gene transcription of the pro-inflammatory cytokine, its receptor, and inflammatory proteins. At the same time, they invoke a negative regulation of type 1 Interferon and the response to viral infections pathways [79].…”
Section: In Vitromentioning
confidence: 99%
“…PON1 genes were associated with Gulf War Syndrome whose complaints of olfactory dysfunction are extensively shared with those of MCS [39]. On the other hand, the overlapping symptoms among MCS spectrum disorders have been found to possibly share some common pathogenetic features such as increased nitric oxide/peroxynitrite levels [57] and its consequences on the olfactory pathways [93]. In light of this, SOD2 genetic polymorphisms, which may be considered genetic determinants of MCS risk [40,[42][43][44]52], seem to be connected to the loss of efficiency of detoxification systems, disturbances of free radical/antioxidant homeostasis, and increased production of inflammatory cytokines [31,48,94].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, SOD2 genetic polymorphisms, which may be considered genetic determinants of MCS risk [40,[42][43][44]52], seem to be connected to the loss of efficiency of detoxification systems, disturbances of free radical/antioxidant homeostasis, and increased production of inflammatory cytokines [31,48,94]. Interestingly, it has also recently been reported that gene variants of NOS2 are associated with the alteration of NO levels in inflammatory bowel disorders, asthma, atopy, olfactory dysfunction, and migraine [57,93,95,96], all of which are comorbidities shared by environmental sensitivity illnesses [57].…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT showed that the application of ozone on the gingival graft surgery site improved the patient's Or quality of life, as well as improved healing along with lower pain intensity (Taşdemir et al, 2016). Ozone, due to its antioxidant effect (Vanni et al, 2016), has had positive effects in the treatment of cardiovascular diseases, improving the patient's prognosis, such as increasing oxygenation in ischemic sites, as has been demonstrated by a RCT to be beneficial in coronary artery disease and heart failure (Martínez-Sánchez et al, 2012) and showed in a clinical trial to treat peripheral arterial disease (Coppola et al, 2002), besides, reviewed by Mauro et al (2019), ozone also showed to be beneficial in the prevention of ischemic damage in an in vitro experiment of ischemia (Frosini et al, 2012) and in a myocardial infarction animal model (Di Filippo et al, 2010). In chronic inflammatory diseases, the use of ozone therapy as an adjuvant has been shown to improve the reference treatment of back pain in patients studied under an RCT (Andrade et al, 2019;reviewed by Bocci et al, 2015).…”
Section: Multiple and Systemic Sclerosismentioning
confidence: 99%